2014
DOI: 10.1371/journal.pone.0091883
|View full text |Cite
|
Sign up to set email alerts
|

Independent Evolutionary Origin of fem Paralogous Genes and Complementary Sex Determination in Hymenopteran Insects

Abstract: The primary signal of sex determination in the honeybee, the complementary sex determiner (csd) gene, evolved from a gene duplication event from an ancestral copy of the fem gene. Recently, other paralogs of the fem gene have been identified in several ant and bumblebee genomes. This discovery and the close phylogenetic relationship of the paralogous gene sequences led to the hypothesis of a single ancestry of the csd genetic system of complementary sex determination in the Hymenopteran insects, in which the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 52 publications
2
40
0
Order By: Relevance
“…Furthermore, these primary signals seem to be rapidly evolving, as they derive from different origins such as from gene duplication or allelic variation (Bopp et al, 2014). Among closely related species like Apis and Bombus, gene duplication of fem occurred independently (Koch et al 2014) and likely led to different functions. Therefore, it is reasonable to argue that the evolution of A. florea and A. mellifera/A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, these primary signals seem to be rapidly evolving, as they derive from different origins such as from gene duplication or allelic variation (Bopp et al, 2014). Among closely related species like Apis and Bombus, gene duplication of fem occurred independently (Koch et al 2014) and likely led to different functions. Therefore, it is reasonable to argue that the evolution of A. florea and A. mellifera/A.…”
Section: Discussionmentioning
confidence: 99%
“…dorsata seems likely. The frequent and independent duplication of fem in Hymenopteran lineages (Geuverink and Beukeboom, 2014;Koch et al, 2014) (Bee10Genome consortium, Kapheim et al, 2015) seems to be a general phenomenon, which may be of broader relevance to better understand the evolution of sex determination pathways in other insect species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). This matches a pattern observed in bumblebees and ants (Schmieder et al ., ; Privman et al ., ; Koch et al ., ). The tra homologue in honeybees ( Ap.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, previously reported data suggested that only CSD species have duplicated tra genes (Schmieder et al , ). Besides, studies of tra in the Chalcidoidea and Symphyta are few (Schmieder et al ., ; Privman et al ., ; Koch et al ., ).…”
Section: Introductionmentioning
confidence: 97%